Exposure to phenols, parabens and UV filters: Associations with loss-of-function mutations in the filaggrin gene in men from the general population - Joensen, Ulla N.; Jørgensen, Niels; Thyssen, Jacob P.; Petersen, Jørgen Holm; Szecsi, Pal B.; Stender, Steen; Andersson, Anne-Maria; Skakkebæk, Niels E.; Frederiksen, Hanne (Environment international, 2017)
Filaggrin is an epidermal protein that is important for normal skin barrier functions. Up to 10% of Europeans and Asians carry filaggrin gene (FLG) loss-of function mutations that appear to facilitate trans-epidermal penetration of certain chemicals. We previously showed that mutation carriers have higher internal exposure to certain phthalates, compared to controls, and hypothesized that they could have increased trans-epidermal penetration of other chemicals. We investigated exposure to non-persistent chemicals in young Danish men with and without FLG mutations. Concentrations of eight simple phenols, six parabens and nine UV filters were analysed in urine from 65 FLG loss-of-function mutation carriers and 130 non-carriers (controls). Regression analyses, controlling for urinary dilution and confounders, were performed to estimate associations between FLG mutation status and chemical concentrations in urine. FLG mutation carriers had 80% (13–180%) higher urinary concentrations of methyl paraben (MeP) and 91% (13–219%) higher concentrations of n-propyl paraben (n-PrP) than controls. For 13 compounds, levels were higher in FLG mutation carriers, although differences were only statistically significant for MeP and n-PrP. Combined statistical analysis of concentrations of all the 18 compounds that were detectable in >10% of subjects, suggested that concentrations were generally higher in mutation carriers (p=0.03). FLG loss-of-function mutation carriers have a higher internal exposure to some non-persistent chemicals, independently of atopic dermatitis. This may be due to increased trans-epidermal absorption and/or higher exposure, and mutation carriers may constitute a group susceptible to increased absorption of chemicals and topical medication. •Filaggrin is crucial to skin barrier function; deficiency may increase penetration of chemicals.•Filaggrin gene (FLG) loss-of function mutations are found in up to 10% of the general population.•We found that FLG mutation carriers had higher internal exposure to parabens compared to controls.•Combined analysis of phenols, UV filters and parabens showed that FLG carriers were more exposed.•Trans-epidermal absorption of chemicals and medication could be higher in FLG mutation carriers.